Controlling of Hysteresis by Varying ZnO-Nanoparticles Amount in P3HT:ZnO Hybrid Thin-Film Transistor: Modeling - Ba, M.; Mansouri, S.; Jouili, A.; Yousfi, Y.; Chouiref, L.; Jdir, M.; El Mir, L. (Springer, 2023)
In this research, we present the production of series of bottom-gate/bottom-contact hybrid thin-film transistors by utilizing a blend of poly(3-hexylthiophene) (P3HT) and zinc oxide (ZnO) as active layers. ZnO nanoparticles are used as electron acceptors in hybrid organic-inorganic-based thin-film transistors as well as electron extraction materials. The nanoparticles of ZnO were produced by the sol-gel protocol. The P3HT:ZnO nanocomposite layers were deposited on silicon dioxide using the spin-coating method. The experimental study indicated that the hysteresis phenomenon of the components can be controlled by varying the amount of ZnO nanoparticles in P3HT:ZnO hybrid blend active layers. As a result, a major improvement of electron transport was observed with the increase of ZnO nanoparticles amount in the active layer, indicates that trapping was reduced in the P3HT:ZnO/SiO2 insulator interface. Furthermore, with increasing the ZnO nanoparticles concentration in the active layer, a critical improvement in the reduction of the trap density at the active layer/SiO2 interface was noticed even without using a dielectric surface treatment. Therefore, these results indicate that the incorporation of ZnO nanoparticles into the P3HT polymer has a crucial role in reducing the trap density in the active layer at the active layer/SiO2 insulator interface, thereby allowing the enhancement the transistor efficiency in terms of carrier mobility, on/off current ratio, threshold voltage, sub-threshold voltage, interface trapped, and density trapped carriers. The fabricated organic thin-film transistors, with significant hysteresis depended on ZnO nanoparticles in the active layer, prove a high possibility to use them for low-cost non-volatile memory thin-film transistors and sensing array applications. The best electrical performance was obtained with the OFET-PZ100 device. Finally, the output characteristics for this thin-film transistor was reproduced by using an analytic model, and good consistency between the different results has been illustrated. [GRAPHICS] .
Keywords: OFET; P3HT; ZnO hybrid blend; optical characterization; ZnO-electronic materials effects; hysteresis; modeling